Visual eWOM Usefulness and Credibility: The Antecedents and Consequences - Whony Rofianto; Desta Atasyah Kornelys; Muhammad Rifkhansyah (Jurnal Ilmu Manajemen & Ekonomika, 2017)
Nowadays the practice of spreading and utilizing eWOM increasingly prevalent. A lot of examination on eWOM effectiveness has been done, but it is still fragmented and overlook the potential of Visual eWom (VeWOM). Departing from the electronic word-of-mouth communication framework this research attempts to provide empirical evidence on the eWOM credibility-forming aspect and its implications toward eWOM adoption rate in the context of VeWOM video "unboxing". This research was conducted by a descriptive-explanatory approach using primary data, collected through a cross-sectional online survey. The hypothesis testing is performed by analyzing structural model estimation result through Structural Equation Modeling (SEM) approach on 105 sample data of YouTube video-sharing site viewers. The proposed structural model involves three exogenous variables and three endogenous variables. The estimation results of the structural model indicate that VeWOM argument quality has a positive impact on VeWOM usefulness. Meanwhile, communicator expertise and trustworthiness proved to encourage the formation of VeWOM credibility. On the other hand, this study also proved the positive impact of VeWOM credibility on VeWOM adoption, however, the positive effect of VeWOM usefulness on VeWOM adoption was not proven in this study